2017
DOI: 10.1111/1468-5973.12206
|View full text |Cite
|
Sign up to set email alerts
|

Canadian citizens volunteering in disasters: From emergence to networked governance

Abstract: How to improve coordination between formal and unaffiliated or spontaneous volunteers after emergencies is currently an international question with a high profile. Drawing on international disaster management literature and experiences and recent crisis events in Canada, our analysis examines four Canadian case studies to show that the inclusion of citizens in EM is becoming indispensable, as simultaneously as the frequency and intensity of natural disasters are seen to be growing due to climate change, and ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…This study relies heavily on previous disaster and crisis management research, particularly on those parts of the literature that discuss volunteerism. Researchers have long been interested in the social behavior that immediately follows crises and studies have repeatedly observed the important roles of different volunteers and volunteer organizations (Fritz & Mathewson, 1957;Lowe & Fothergill, 2003) A recurring conclusion is that in crises, ordinary citizens and volunteer organizations are resourceful and they draw on a wide array of skills to help themselves and others (Waldman, Yumagulova, Mackwani, Benson, & Stone, 2018).…”
Section: Previous Research On Crisis Volunteerismmentioning
confidence: 99%
“…This study relies heavily on previous disaster and crisis management research, particularly on those parts of the literature that discuss volunteerism. Researchers have long been interested in the social behavior that immediately follows crises and studies have repeatedly observed the important roles of different volunteers and volunteer organizations (Fritz & Mathewson, 1957;Lowe & Fothergill, 2003) A recurring conclusion is that in crises, ordinary citizens and volunteer organizations are resourceful and they draw on a wide array of skills to help themselves and others (Waldman, Yumagulova, Mackwani, Benson, & Stone, 2018).…”
Section: Previous Research On Crisis Volunteerismmentioning
confidence: 99%
“…The civil protection and preparedness sector needs to adapt its organizations to such changes, for example, by providing online platforms where citizens can register without being a member of an organization (Schmidt, Wolbers, Ferguson, & Boersma, 2017) or, more generally, by building structures of "networked governance" to include citizens (Waldman, Yumagulova, Mackwani, & Benson, 2017).…”
Section: The Inclusion Of Members Of Voluntary Emergency Organizationsmentioning
confidence: 99%
“…A number of examples for significant, and at times life‐saving, informal citizen responses can be found in Scanlon, Helsloot, and Groenendaal (). However, these activities are often recognized as a mixed blessing (Barsky, Trainor, Torres, & Aguirre, ) or double‐edged sword (Strand & Eklund, in press) by professional actors due to differences in training, skills, safety procedures, and situational perceptions (Barsky et al., ; Fernandez, Barbera, & van Dorp, ; Kendra & Wachtendorf, ; Skar et al., ; Waldman et al., in press). Several authors (Helsloot & Ruitenberg, ; Kvarnlöf & Johansson, ) state that professional organizations and disaster managers consider informal responses to be primarily “problems that must be controlled” (Wenger, : 12).…”
Section: Background and Research Overviewmentioning
confidence: 99%
“…The reasons as to why unaffiliated responders have yet to be properly integrated are many and diverse. On the one hand, it is argued mainly by professional responders that cooperation is prevented as a result of predominantly practical hindrances such as differing training, differing knowledge, uncertainties regarding lawful authority and liability, or as fallout from organizational structures (Waldman, Yumagulova, Mackwani, Benson, & Stone, in press). On the other hand, scientific discourse gives clues with the attention and particular insights it has gleaned regarding disaster myths (Auf der Heide, ): myths which draw an empirically false portrayal of civilian populations in disaster situations and serve as a major impediment to better integration.…”
Section: Introductionmentioning
confidence: 99%